Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - 11.4 - Complex Numbers - Problem Set 11.4 - Page 493: 47



Work Step by Step

We multiply each term of the first complex number with the second complex number and then simplify: $(-1-4i)(-2-7i)$ =$-1(-2-7i)-4i(-2-7i)$ =$2+7i+8i+28i^{2}$ =$2+15i+28(-1)$ [We substitute -1 in place of $i^{2}$ as $i^{2}=-1$] =$2-28+15i$ =$-26+15i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.